Annual Danish language essay competition - Ангелова, Лора; Текелова, Михаела; Боризанов, Мартин (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
Since 2015, the Hans Christian Andersen Centre for Research and Information at Sofia University St. Kliment Ohridski, the Embassy of the Kingdom of Denmark in Sofia, and the Danish Agency for Culture and Palaces have organized an annual essay competition in Danish. This year’s edition of the competition was held under the title “The Things I Love…”. Participants were asked to write an essay inspired by Hans Christian Andersen’s 1830 poem “The Things I Love” (Hvad jeg elsker). The year 2025 marks the 150th anniversary of the famous Danish writer’s death.